EDUKASI KEBERSIHAN DIRI DAN KESEHATAN LINGKUNGAN PADA PROGRAM KEMITRAAN MASYARAKAT PEMBENTUKAN POSKESTREN DI PONDOK PESANTREN AL HIKAM BANGKALAN MADURA - Handayani Handayani; Rizqi Putri Nourma Budiarti; Tri Wahyuni Bintarti (UNUSA Press, 2019)
Abstract Community service activities are expected to broaden the horizons by providing Personal Hygiene and Environmental Education at Al-Hikam Islamic Boarding School, Bangkalan, Madura. The targeted output plan is to increase public awareness about personal hygiene and environmental hygiene including healthy room criteria. The implementation of this socialization has the target of the community, namely students and female students who are members of the Husada Santri cadre in hopes of increasing public knowledge about healthy homes and raising awareness to pay more attention to good spatial planning according to criteria of healthy homes. Husada Santri cadres consist of junior high, high school and vocational levels. This intervention in community service is carried out with the implementation method, namely counseling. With this method, it is expected that understanding, knowledge and awareness about personal hygiene and environmental cleanliness can be increased. After completing the community service socialization intervention, the final step is to conduct an evaluation. The evaluation was designed by comparing the conditions of initial knowledge before the intervention with the increase in knowledge after the implementation of the intervention. Photo shoot of community knowledge about personal hygiene and environmental hygiene by using simple pre-test and post-test of each individual